State and local government - "Engel, Michael" (New York, 1999)
State and Local Government" takes an innovative approach to the study of state and local government by offering readers the means to develop their own points of view on its institutions, processes, and policies. Federalism, governmental structure, the party and electoral systems, and methods of citizen influence are described and then evaluated in the context of the opposing perspectives of conflict and consensus theories. State and local policies on public finance, economic development, welfare, and education are examined and then critiqued from the points of view of conservative, liberal, and socialist ideologies. The result is a book that not only informs readers on the facts of state and local government and politics, but also challenges them to think critically and analytically about those facts, and then helps them to draw conclusions about how well those processes and institutions are working.
Keywords: State government-United states